Shaykh Yūsuf al-Qaraḍāwī: spiritual mentor of Wasaṭī Salafism - Polḳah, Śagi (Modern intellectual and political history of the Middle East, 2019)
List of illustrations -- Acknowledgments -- Abbreviations -- Note on transliteration and translations -- The clash within Islam: a sampling of representative quotes -- Introduction: Wasaṭī Islamism -- 1. Wasaṭiyya, an innovating Salafism: reform (iṣlāḥ) and renewal (tajdīd) -- 2. The Wasaṭiyya school as shaped by Yūsuf al-Qaraḍāwī: from the Muslim Brotherhood to Wasaṭiyya -- 3. al-Qaraḍāwī, al-Azhar, and the Muslim Brotherhood -- 4. Wasaṭiyya: between the Muslim Brotherhood and Jihadi Salafism -- 5. The conception of jihad: Wasaṭ apologetics, Jihadi Salafī selective reading, and liberal claims of distorted interpretation -- 6. Principles of Wasaṭ judicial decisions: Salafī and Wasaṭ dogmatism versus liberal openness to reform -- Conclusion: Islam at a crossroads -- Appendix A. Fundamental principles of the Wasaṭiyya and renewal movement -- Appendix B. The neoliberal platform by Shākir al-Nābulsī -- Glossary -- Notes -- Bibliography -- Index